Cholangioscopy-guided lithotripsy vs. conventional therapy for complex bile duct stones: a systematic review and meta-analysis - GALETTI,Facundo (2020)
ABSTRACT Introduction: Endoscopic removal of common bile duct stones has a high success rate ranging from 85% to 95%. Bile duct stones >15 mm are difficult and frequently require lithotripsy. Peroral cholangioscopy (POC) allows lithotripsy with similar success rates. Aim: To determine the efficacy and safety of cholangioscopy-guided lithotripsy used in the treatment of difficult to remove bile duct stones vs. conventional therapy. Methods: Search was based in Medline, Embase, Cochrane Central, Lilacs/Bireme. Studies enrolling patients referred for the removal of difficult bile duct stones via POC were considered eligible. Two analyses were carried out separately, one included randomized controlled trials (RCTs) and another observational studies. Results: Forty-six studies were selected (3 RTC and 43 observational). In the analysis there was no statistical significant difference between successful endoscopic clearance (RD=-0.02 CI: -0.17, 0.12/I²=0%), mean fluoroscopy time (MD=-0.14 CI -1.60, 1.32/I²=21%) and adverse events rates (RD=-0.06 CI: -0.14, 0.02/I²=0%), by contrast, the mean procedure time favored conventional therapy with statistical significance (MD=27.89 CI: 16.68, 39.10/I²=0%). In observational studies, the successful endoscopic clearance rate was 88.29% (CI95: 86.9%-90.7%), the first session successful endoscopic clearance rate was 72.7 % (CI95: 69.9%-75.3%), the mean procedure time was 47.50±6 min for session and the number of sessions to clear bile duct was 1.5±0.18. The adverse event rate was 8.7% (CI95: 7%-10.9%). Conclusions: For complex common bile duct stones, cholangioscopy-guided lithotripsy has a success rate that is similar to traditional ERCP techniques in terms of therapeutic success, adverse event rate and means fluoroscopy time. Conventional ERCP methods have a shorter mean procedure time.